Complement complex 1 subunit q‐mediated hepatic stellate cell activation with connective tissue growth factor elevation is a prognostic factor for survival in rat and human chronic liver diseases. Issue 12 (5th October 2022) - Eguchi, Akiko; Iwasa, Motoh; Sugimoto, Ryosuke; Tempaku, Mina; Yoshikawa, Kyoko; Yoshizawa, Naohiko; Povero, Davide; Sugimoto, Kazushi; Hasegawa, Hiroshi; Takei, Yoshiyuki; Nakagawa, Hayato
Abstract: Complement complex 1 subunit q (C1q) has multiple functions, including cell migration, in addition to its traditional complement‐activating effect. Research shows C1q is a ligand for frizzled receptors (FZDs). FZD‐induced yes‐associated protein (YAP)/transcriptional co‐activator with PDZ‐binding motif (TAZ) alternate Wnt signaling activation induces connective tissue growth factor (CTGF) production and hepatic stellate cell (HSC) activation. However, no study exists in which C1q directly induces CTGF in HSCs. Here, we investigated the role of C1q in HSC activation. Human HSCs (LX2) were incubated with C1q to assess HSC activation. C1q and fibrotic markers were assessed using immunohistochemistry, immunoblotting, and quantitative reverse‐transcription polymerase chain reaction in cirrhotic rats administered CCl4 for 21 weeks. Serum C1q, liver function, and fibrosis score were measured in 91 patients with chronic liver disease. The correlations between serum C1q and liver function, fibrosis score, and survival prognosis were examined. C1q‐activated LX2s showed morphologic changes, up‐regulation of CTGF, tissue inhibitors of metalloproteinases ( TIMP‐1 ),  and alternate Wnt signal genes FZD2, TAZ, and cysteine‐rich angiogenic inducer 61 ( Cyr61 ). Cirrhotic rat liver C1q expression correlated with the Azan‐positive area and expression of CTGF, TIMP‐1, hyaluronan synthase ( HAS )1, HAS3, and CD44 . Expression of C1q protein and C1q, CTGF, and TIMP‐1 genes were higher in deceased cirrhotic rat livers compared to surviving rats. Human serum C1q levels increased in liver cirrhosis compared to chronic hepatitis and correlated with liver fibrosis and functional markers. Ten patients suffered liver‐related death over a 66‐month observation period. The C1q cut‐off value (11 mg/dl) showed patients with serum values < 11 mg/dl had longer rates of survival compared to C1q ≥ 11 mg/dl. Conclusion : C1q‐mediated HSC activation in liver fibrosis is associated with CTGF elevation. Additionally, serum C1q may be diagnostic for survival in human chronic liver diseases. Abstract : No study exists in which C1q directly induced CTGF in HSCs. We therefore investigated C1q's role in HSC activation and found that C1q activated HSC, LX2 cells, with CTGF elevation through alternative Wnt signaling pathway and C1q levels were significantly associated with the advanced liver fibrosis and survival in cirrhotic rat and human.image